2016
DOI: 10.4209/aaqr.2016.08.0358
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on HCCI Combustion in a Small Engine with Various Fuels and EGR

Abstract: Because Asian countries have a large number of motorcycles, motorcycle engine exhaust emission poses a major problem in the region. Homogeneous charge compression ignition (HCCI) is a promising combustion technology with high efficiency and low nitrogen oxide emission. This study investigated the combustion characteristics of HCCI in a 150 cc motorcycle engine with three types of dual fuel. The main fuels consisted of dimethyl ether (DME), kerosene, and nheptane, and gasoline was the additive fuel. External ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The fuel for HCCI operation in an SI engine should have a low autoignition temperature. Previous research [34] has concluded that DME, the properties of which are listed in Table 3, is a favorable choice for this. The cetane number of DME is 60, higher than that of diesel fuel (i.e., .…”
Section: Methodsmentioning
confidence: 99%
“…The fuel for HCCI operation in an SI engine should have a low autoignition temperature. Previous research [34] has concluded that DME, the properties of which are listed in Table 3, is a favorable choice for this. The cetane number of DME is 60, higher than that of diesel fuel (i.e., .…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, HCCI poses some unresolved challenges, including combustion phase control, narrow operating range, cold start, high noise, and homogeneous charge preparation [27]. The most popular approaches for combustion phase control are exhaust gas recirculation (EGR) and the use of dual fuel [28][29][30][31]. Dual fuel involves a combination of diesel-and gasoline-like fuels.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, gasoline-like fuels, such as isooctane, ethanol, methanol, liquefied petroleum gas, and butanol, have a high-octane number and cannot autoignite easily. Gasoline-like fuels can be used as ignition suppressors, whereas diesel-like fuels function as ignition improvers [31]. The ratio of these two types of fuels has a significant effect on combustion phasing.…”
Section: Introductionmentioning
confidence: 99%